In the unlikely event - Blume, Judy (Alfred A. Knopf, 2015)
In 1987, Miri Ammerman returns to her hometown of Elizabeth, New Jersey, to attend a commemoration of the worst year of her life -- when a succession of airplanes fell from the sky, leaving her community reeling.